Новые виды веснянок сем. Nemouridae (Plecoptera) с Дальнего Востока - Жильцова, Л.А. (Вестник зоологии, 1982)
Twenty six stonefly species of the family Nemouridae are knownto occur in the Par East. The genera Protonemura and Nemoura are represen t e d h e r e b v 2 a n d b snecies. respectively. Three species are describedas new. Nemoura brevicercia sp. :n. cerci short, male epiproctal tip with a longprocess, female genital plate triangular. N. gracilis sp. n.: paraproctal tip bears an additional lateral protuberance; medial paraproctalmargin with a deep incision; slender cerci with laterallycurved tips, distinct shape of the epiprocta! sclerites. Protonemoura ermolenRoi sp. n.: shows some Similarities with Japanese P. l a R a n a v e n o . differs by the presence of distal paraproctal protuberance and distinct structure of medial male appendages.